RHYTHM IN MONOLOGUE VIDEO BY CHARLIE CHAPLIN - Amanda, Gita; Oktapiani, Rosi (PROJECT (Professional Journal of English Education), 2019)
The aim of this article is to know about the rhythm of the monologue video by the dialogue of Charlie Chaplin. Rhythm is a characteristic sound that have a strong beat and a weak beat, the writers will try to proof whether it can imitated well or can not imitated well by some of foreign learners. The writers will make a transcript of a dialogue in the last part of the movie The Great Dictator, and as a foreign learner, the writers will try to imitated Charlie Chaplin by watching and listening the character sound that Charlie Chaplin has. The last, the writers will discus the result to find where is the beat that hard to imitated or which the dialogue that hard or easy to imitated. The method of this article is using a qualitative method because this article is about non-numerical language and also focus on analyzing the data.